Esterase patterns and phylogenetic relationships of species and strains included in the Drosophila buzzatii cluster - Lapenta, A. S.; De Campos Bicudo, H. E.M. [UNESP]; Ceron, C. R. [UNESP]; Cordeiro, J. A. [UNESP] (My University, 1998)
Ten strains of two species in the Drosophila buzzatii cluster (D. serido and D. seriema) were examined as to esterase patterns using polyacrylamide gel electrophoresis. The migration rate of esterases, and their substrate specificity to alpha and beta naphthyl acetates, were analysed. Other esterase features such as inhibition behaviour, presence in males and females and location in the head, thorax or abdomen of flies, were also examined. The present data, together with results obtained by others for eight strains of D. koepferae, D. serido, D. seriema and D. buzzatii, show that 69 bands have been detected in the eighteen strains studied. This total number of bands was used for comparison of strains and species by similarity index, analysis of dependence and cluster analysis. The comparisons confirmed the existence of a high degree of similarity among D. seriema strains and among D. koepferae strains, but indicated differentiation among the D. serido strains. Two strains (D69R2 and D69R5) which differed from the others of the latter species, showed closer affinities with D. buzzatii, which indicates the need for further work on those strains classified as D. serido.
Keywords: Drosophila buzzatii cluster; Esterases; Phylogenetic relationships